Analisis Determinan Kepatuhan Wajib Pajak dalam Membayar Pajak Hotel, Restoran, dan Hiburan di Kota Medan - Muhammad Fitri Rahmadana (Outline Publisher, 2022)
Regional tax revenue in Medan City has experienced a significant increase, thereby rendering local taxes as the primary source of financing for regional expenditures. Despite the limited fiscal capacity that stems from local revenue, local taxes continue to play a crucial role in enhancing tax revenue in Medan City. Pursuant to Law Number 28 Year 2011, the self-assessment system for collecting hotel, restaurant and entertainment taxes underscores the significance of taxpayer awareness in compliance with tax obligations and rights. This study aims to achieve two objectives. Firstly, to analyze the impact of tax knowledge, service quality, and tax audit on taxpayer awareness concerning payment of hotel taxes, restaurant taxes, and entertainment taxes in Medan City. Secondly, to examine the impact of tax knowledge, service quality, tax inspection, and taxpayer awareness on taxpayer compliance with respect to the payment of hotel taxes, restaurant taxes, and entertainment taxes in Medan City. The study employs quantitative research methods, utilizing both primary and secondary data sources obtained from the Medan City Revenue Service. Questionnaires were used to collect data, and accidental sampling was employed. Descriptive analysis and path diagram analysis were employed as analytical tools. The results of the hypothesis testing conducted by path analysis indicate that tax knowledge, service quality, and tax audits have a positive effect on taxpayer awareness of paying hotel taxes, restaurant taxes, and entertainment taxes in Medan City. Service quality and tax audits do not impact taxpayer compliance with paying hotel, restaurant, and entertainment taxes in the City of Medan. However, tax knowledge, tax inspection, and taxpayer awareness have a positive impact on taxpayer compliance with paying hotel taxes, restaurant taxes, and entertainment taxes in Medan City. This is due to the significant contribution made by hotel taxes, restaurant taxes, and entertainment taxes to local taxes in Medan City.